Correlations between different hardened properties of high-strength self-consolidating concrete including palm oil fuel ash - Safiuddin, M.; Salam, M.A.; Jumaat, Mohd Zamin (2012)
Palm oil fuel ash is considered as an agro-waste material in Malaysia. Various investigations have been conducted on the use of palm oil fuel ash as a supplementary cementing material for concrete. In the present study, palm oil fuel ash was used as a partial replacement of normal portland cement to produce high-strength self-consolidating concrete. In total, twenty (20) self-consolidating concrete mixes were prepared by varying water to binder ratio, palm oil fuel ash content, and high-range water reducer dosage. Palm oil fuel ash was used by replacing 0-30 of normal portland cement by weight at the water to binder ratios ranging from 0.25 to 0.40. The compressive, splitting tensile and flexural strengths, modulus of elasticity, ultrasonic pulse velocity, and porosity of various self-consolidating concrete mixes were investigated. However, the correlations between the hardened properties of concrete were emphasized in this study. The experimental findings revealed that strong correlations exist between different hardened properties of high-strength self-consolidating concrete.